2022
DOI: 10.1097/pcc.0000000000002833
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Entrustable Professional Activities in Pediatric Cardiac Critical Care*

Abstract: OBJECTIVES: Define a set of entrustable professional activities for pediatric cardiac critical care that are recognized as the core activities of the subspecialty by a diverse group of pediatric cardiac critical care physicians and that can be broadly and consistently applied irrespective of training pathway.DESIGN: Mixed methods study with sequential integration of qualitative and quantitative data. SETTING:Structured telephone interviews of pediatric cardiac critical care medical directors at Pediatric Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…3,5,14 A recent survey of paediatric critical care medicine directors indicated that approximately 33% of cardiac ICU staff physicians are double-boarded in paediatric critical care medicine and cardiology, 12.5% underwent paediatric critical care medicine fellowship and a 1-year cardiac ICU fellowship, 30% underwent cardiology fellowship in addition to a 1-year cardiac ICU fellowship, and 21% underwent paediatric critical care medicine fellowship with no additional training (including those who were practising long before the addition of the 1-year cardiac ICU and dual fellowship training pathways became readily available). 16 The 1-year paediatric cardiac critical care fellowship even has standardised training guidelines now; however, dual boarding in cardiology and paediatric critical care medicine remains the gold standard. 1 While paediatric residents commonly staff mixed units, paediatric critical care medicine fellows are predominant learners in cardiac ICUs, perhaps allowing for more fellow practice autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,14 A recent survey of paediatric critical care medicine directors indicated that approximately 33% of cardiac ICU staff physicians are double-boarded in paediatric critical care medicine and cardiology, 12.5% underwent paediatric critical care medicine fellowship and a 1-year cardiac ICU fellowship, 30% underwent cardiology fellowship in addition to a 1-year cardiac ICU fellowship, and 21% underwent paediatric critical care medicine fellowship with no additional training (including those who were practising long before the addition of the 1-year cardiac ICU and dual fellowship training pathways became readily available). 16 The 1-year paediatric cardiac critical care fellowship even has standardised training guidelines now; however, dual boarding in cardiology and paediatric critical care medicine remains the gold standard. 1 While paediatric residents commonly staff mixed units, paediatric critical care medicine fellows are predominant learners in cardiac ICUs, perhaps allowing for more fellow practice autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also provide readers with an Appendix of learning objectives for subspecialty education and training in PCCCM that is well worth studying closely. Second, a mixed-methods report using interviews of medical directors involved with the pediatric cardiac critical care consortium (PC 4 ) as well as other physicians in the field (5). Here, the objective was to identify and define the core training entrustable professional activities that could be applied to practice in PCCCM.…”
Section: Tabbutt S Krawczeski C Mcbride M Et Al: Standardized Trainin...mentioning
confidence: 99%
“…While the framework is thorough, it is time- and resource-intensive to track EPAs for every fellow during their training [ 15 ]. There has also been the creation of EPAs pertaining to pediatric cardiology subspecialties, such as cardiac critical care [ 38 ]. The inherent flexibility of the EPA framework allows program directors to determine how they wish to utilize EPAs in their fellowship program and therefore limits assessing their efficacy and utility [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%